2020
DOI: 10.1161/circresaha.119.316369
|View full text |Cite
|
Sign up to set email alerts
|

MCUb Induction Protects the Heart From Postischemic Remodeling

Abstract: Rationale: Mitochondrial Ca 2+ loading augments oxidative metabolism to match functional demands during times of increased work or injury. However, mitochondrial Ca 2+ overload also directly causes mitochondrial rupture and cardiomyocyte death during ischemia-reperfusion injury by inducing mitochondrial permeability transition pore opening. The MCU (mitochondrial Ca 2+ uniporter) mediates mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 42 publications
2
45
0
Order By: Relevance
“…Restraining [Ca 2+ ] m influx via the upregulation of MICU1 protected the heart from I/R injury [3,50]. MCUb was not expressed at baseline, but was upregulated when sensing calcium elevation in the cytoplasm [21]. MCUb overexpression reduced mPTP opening and decreased infarct size following IR injury [21,26].…”
Section: Discussionmentioning
confidence: 98%
“…Restraining [Ca 2+ ] m influx via the upregulation of MICU1 protected the heart from I/R injury [3,50]. MCUb was not expressed at baseline, but was upregulated when sensing calcium elevation in the cytoplasm [21]. MCUb overexpression reduced mPTP opening and decreased infarct size following IR injury [21,26].…”
Section: Discussionmentioning
confidence: 98%
“…MCUB is a necessary part of a protective response against mitochondrial Ca 2+ overload during cardiac injury and ischemia 87 . Mcub -/- mice displayed increased cardiac remodelling and ischemic injury as a result of increased mitochondrial Ca 2+ uptake 88 . Although more research is required to fully understand the role of MCUB in severe COVID-19 pathogenesis, a decreased level of serum calcium has been suggested as a biomarker for increased COVID-19 severity and ARDS 89 .…”
Section: Discussionmentioning
confidence: 98%
“…Using mice with cardiomyocyte-specific overexpression or deletion of MCUB, Huo et al . 56 showed that MCUB is inducible and limits mitochondrial Ca 2+ influx after IR, preventing mitochondrial permeability transition pore (mPTP) opening and protecting the myocardium. Interestingly, hindlimb remote ischemic preconditioning increased MCUB expression in the heart and decreased mitochondrial Ca 2+ uptake.…”
Section: Powering the Heart—mitochondria And Metabolismmentioning
confidence: 99%